2020
DOI: 10.1002/chem.201905264
|View full text |Cite
|
Sign up to set email alerts
|

Spherical Aromaticity of All‐Metal [Bi@In8Bi12]3−/5− Clusters

Abstract: The chemical bonding of Zintl clusters is stilla n evolving and hot topic in modern chemistry.I nt his paper we synthesized an ovel [K([2.2.2]crypt)] 4 [In 8 Bi 13 ]c omplex in a condensed phase. The quantum chemical calculations and X-ray data revealed that the compound consists of the 1:1 mixture of [Bi@In 8 Bi 12 ] 3À and [Bi@In 8 Bi 12 ] 5À clusters. To the date, those clusters are the largest binary clusters composed of In and Bi elements. Herein, we introduce as pherical aro-matic description of chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 47 publications
(120 reference statements)
0
18
0
Order By: Relevance
“…4 ). It is depicted by 3c–2e and 5c–2e bonds within the cluster cage, which share common atom centers (certain atoms contribute to both multi-center bonds), resulting in a spherical-like shielding surface as observed for other Zintl-clusters and intermetalloids 41 , 53 . This situation is similar to the [Ge 9 ] 4− case 42 , where the presence of multiple σ-aromatic boding elements, sharing common atom centers, generates a spherical-like aromatic behavior given by the characteristic shielding surface (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…4 ). It is depicted by 3c–2e and 5c–2e bonds within the cluster cage, which share common atom centers (certain atoms contribute to both multi-center bonds), resulting in a spherical-like shielding surface as observed for other Zintl-clusters and intermetalloids 41 , 53 . This situation is similar to the [Ge 9 ] 4− case 42 , where the presence of multiple σ-aromatic boding elements, sharing common atom centers, generates a spherical-like aromatic behavior given by the characteristic shielding surface (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 96%
“…The AdNDP method can represent a chemical bonding pattern in terms of both Lewis bonding elements (lone pairs (1c–2e) and 2c–2e bonds) as well as delocalized bonding elements (such as nc–2e ( n > 2) bonds), while the latter are usually associated with the concepts of aromaticity and antiaromaticity. This technique has been widely used in describing chemical bonding pattern of various Zintl clusters 41 47 . The chemical bonding of [Sn 2 Sb 5 ] 3− can be entirely described in terms of the classical 1c–2e and 2c–2e bonds (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As an extension to this concept, spherical‐like structures also enable similar properties related historically to π‐planar species, among monolayers, expanded molecules, and other species, which can be explored in different metallic clusters …”
Section: Introductionmentioning
confidence: 99%
“…3. 31 Magnetic measurements of 4 revealed that the oxidation state of the uranium and change of the cluster are best described as [U 4+ @Bi 38 Seminal work in the field was reported by Eichhorn and coworkers in 2003, with the preparation of an onion-skin cluster, [As@Ni 12 @As 20 ] 3− (13). 39 This cluster is comprised of a [As@Ni 12 ] 3− endohedral icosahedron encapsulated by an As 20 dodecahedron.…”
Section: Recent Additions To the Library Of Homoatomic Group 15 Zintl Clustersmentioning
confidence: 99%